Ethnobotanical applications of Spathodea campanulata P. Beauv. (African tulip tree) in Ghana - Boakye, Maxwell Kwame; Agyemang, Alfred Ofori; Gbadegbe, Richard Selase; Quashie, Mawuli; Turkson, Bernard Kofi; Adanu, Kekeli Kodjo; Wiafe, Edward Debrah (Ethnobotany Research and Applications, 2023)
Background: Spathodea campanulata P. Beauv. (Bignoniaceae) is documented to have ethnobotanical potential worldwide, but knowledge about this useful tree to local communities is limited in Ghana. This study was aimed at evaluation of ethnobotanical knowledge of the utilization of S. campanulata among the local population in Ghana. Methods: Data was collected through a semi-structured interviews with 193 participants in the Adaklu District of the Volta Region of Ghana. Ethnobotanical indices were used to quantitatively determine the most culturally important S. campanulata plant parts using the ethnobotanyR package. Results: A total of 25 applications grouped into six use categories from seven S. campanulata parts were observed in this study. The primary use category was material, followed by fuel, medicine, environmental, food additive, and food. Anemia had the highest frequency of mentions, followed by firewood and dyeing of cloth, construction, furniture, and charcoal. The wood had the highest use reports (UR) and cultural importance (CI), while stem bark had the highest number of uses (NU) and cultural value index (CVe). Conclusion: The study showed that the applications and use categories were influenced by the rural nature of communities and lack of availability of services. This study revealed a high-fidelity level for the S. campanulata stem bark to treat anemia, a common ailment in the study region. The study suggests increasing awareness for better promotion and valorization of S. campanulata in Ghana as a source of fuel wood and medicinal purposes. Keywords: ethnobotany, Volta region, anemia, dyeing, construction, furniture, cultural importance